MOLECULAR DOCKING OF D6-ANHYDROERYTHROMYCIN TO rRNA 23S Deinococcus radiodurans AND THE PREDICTION OF ITS ANTIBIOTIC POTENCY - Winarto Haryadi; Umar Anggara Jenie; Retno Sunarminingsih Sudibyo; Harno Dwi Pranowo; Fajar Rakhman Wibowo (Indonesian Journal of Chemistry, 2009)
D6-anhidroeritromisin-A is a new derivative of erythromycin which is synthesized through biosynthetic engineering technique. The molecular docking in rRNA 23S Deinoccocus radiodurans are accomplished to determine the model and strength of binding to the target macromolecule. The molecular docking of erythromycin-A and 6-deoksieritromisin-A to the same macromolecule is used as a control. The docking result of the D6-anhidroeritromisin-A shows that it occupies the same cavity as of the experimental erythromycin-A in the same macromolecule. The binding position of D6-anhidroeritromisin-A is not exactly same as erythromycin-A and 6-deoksieritromisin-A due to the presence of D6 unsaturated double bond. However the hydroxyl group(OH) at C-6 does not have an apparent effect on the binding model to rRNA23S D. radiodurans.